Orientalist Representation of Nepali People, Culture and Landscape: A Critical Discourse Analysis of Kincaid’s Among Flowers: A Walk in the Himalaya - Bhat, Shuv Raj Rana (SCHOLARS: Journal of Arts & Humanities, 2019)
Partly drawing on postcolonial rhetorics and partly drawing insights from critical stylistics and critical discourse analysis, this paper basically explores how Antigua-born-American writer Jamaica Kincaid rhetorically constructs Nepal in a disguised form of a travel writer through her travel narrative Among Flowers: A Walk in the Himalaya. Even though Kincaid is best known as an anti-imperialist, the way she longs for the Garden of Eden and represents Nepali landscape, people, and culture posits that her travel to Nepal is threaded with the rhetoric of Othering, metropolitan culture, and imperial politics. In particular, she looks at the travelled places and people with an imperial eye: nomination, surveillance, negation, debasement, and binary rhetoric.